Engineering mesoporous silica nanoparticles for drug delivery: where are we after two decades? - Vallet-Regí, María; Schüth, Ferdi; Lozano, Daniel; Colilla, Montserrat; Manzano, Miguel (Chemical Society reviews, 2022)
The present review details a chronological description of the events that took place during the development of mesoporous materials, their different synthetic routes and their use as drug delivery systems. The outstanding textural properties of these materials quickly inspired their translation to the nanoscale dimension leading to mesoporous silica nanoparticles (MSNs). The different aspects of introducing pharmaceutical agents into the pores of these nanocarriers, together with their possible biodistribution and clearance routes, would be described here. The development of smart nanocarriers that are able to release a high local concentration of the therapeutic cargo on-demand after the application of certain stimuli would be reviewed here, together with their ability to deliver the therapeutic cargo to precise locations in the body. The huge progress in the design and development of MSNs for biomedical applications, including the potential treatment of different diseases, during the last 20 years will be collated here, together with the required work that still needs to be done to achieve the clinical translation of these materials. This review was conceived to stand out from past reports since it aims to tell the story of the development of mesoporous materials and their use as drug delivery systems by some of the story makers, who could be considered to be among the pioneers in this area.